2011
DOI: 10.1371/journal.pone.0018086
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Precise Quantification of Insulin-Like mRNA Expression in Caenorhabditis elegans

Abstract: Insulin-like signaling regulates developmental arrest, stress resistance and lifespan in the nematode Caenorhabditis elegans. However, the genome encodes 40 insulin-like peptides, and the regulation and function of individual peptides is largely uncharacterized. We used the nCounter platform to measure mRNA expression of all 40 insulin-like peptides as well as the insulin-like receptor daf-2, its transcriptional effector daf-16, and the daf-16 target gene sod-3. We validated the platform using 53 RNA samples p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…These results are consistent with findings in C. elegans , where IIS signaling is thought to be regulated at the level of the ILPs, while intracellular signaling components are always present [41]. However, we did observe developmental regulation of several IIS signaling component transcripts in the post-free living generation, including increases in the transcript abundances for Ss-daf-2 , Ss-age-1 , Ss-pdk-1 , Ss-akt-1 , and Ss-daf-16 (Figure S8).…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with findings in C. elegans , where IIS signaling is thought to be regulated at the level of the ILPs, while intracellular signaling components are always present [41]. However, we did observe developmental regulation of several IIS signaling component transcripts in the post-free living generation, including increases in the transcript abundances for Ss-daf-2 , Ss-age-1 , Ss-pdk-1 , Ss-akt-1 , and Ss-daf-16 (Figure S8).…”
Section: Discussionsupporting
confidence: 92%
“…Because both genes were shown to be up-regulated during L1 diapause and in dauer larvae of wild-type animals [20], they may function as the IIS receptor antagonists. Their down-regulation in starved L1 lin-35/Rb(lf) mutants is consistent with Rb’s role in repressing the IIS pathway.…”
Section: Resultsmentioning
confidence: 99%
“…6C). In a recent study it was reported that endogenous ins-7 is expressed at higher levels than ins-8 throughout development (Baugh et al 2011). ins-7 and ins-8 are less than 1 kb apart in the genome; therefore, in the ins-7(tm1907), the ins-8 gene resides in closer proximity to the (stronger) ins-7 promoter (data not shown).…”
Section: Ins-8 Expression Increases Upon Loss Of Ins-7mentioning
confidence: 86%